Experimentally Induced Bladder Permeability Evokes Bladder Afferent Hypersensitivity in the Absence of Inflammation - Grundy, Luke; Caldwell, Ashlee; Lumsden, Amanda; Mohammadi, Ehsan; Hannig, Gerhard; Greenwood Van-Meervald, Beverley; Brierley, Stuart M. (Frontiers in Neuroscience, 2020)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic urological condition charactersied by urinary urgency, frequency and pelvic pain, that significantly impacts the quality of life for approximately 5% of women. Bladder sensation is coordinated by primary afferent sensory neurons that innervate the bladder wall, translating bladder stretch into signals that travel to the brain via the spinal cord. Whilst the pathophysiology of IC/BPS remains unknown, an increase in the permeability of the bladder urothelium has been proposed as an initiating cause. Here we experimentally increased bladder permeability and tracked bladder afferent sensitivity for up to 28 days. We found that one day after increasing bladder epithelial permeability with in-vivo bladder infusion of protamine sulfate mechanosensitive bladder afferents exhibited significant hypersensitivity to bladder filling. This mechanical hypersensitivity was characterised by significantly increased peak afferent firing rates and a decrease in the activation threshold of individual afferents. Bladder afferent hypersensitivity occurred in the absence of inflammation and changes in bladder muscle compliance, indicating a direct sensitisation of peripheral afferent endings. Bladder afferent mechanosensitive responses to distension returned to control levels by day 7 post-protamine sulfate treatment and remained at control levels at 28-days post-treatment. Here we demonstrate, contrary to the prevailing hypothesis, that increased bladder permeability alone does not induce chronic bladder afferent sensitisation. Whilst experimentally induced changes in bladder permeability are able to induce transient bladder afferent hypersensitivity in the absence of inflammation highly regulated homeostatic mechanisms exist to rapidly repair the urothelial barrier and normalise bladder afferent mechanosensitivity. Together these data suggest that additional pathophysiology is required to induce chronic bladder dysfunction.